Risk of Back Pain in Faculty of Medicine UPN Veteran Jakarta Students During Online Lectures in the 2020 COVID-19 Pandemic Era - Dwi Arwandi Yogi Saputra; Hermawan Saputra; Sutoto Sutoto (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2022)
Online learning is learning that is done without face-to-face but through available platforms. All forms of learning materials are distributed online. Communication is done online and tests are also conducted online. During the Covid-19 pandemic, distance learning using devices such as laptops and smartphones is very much needed to support distance learning activities. This has an impact on increasing the risks that arise such as back pain.